2011
DOI: 10.1242/jeb.051581
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking by protein oxidation in the rapidly setting gel-based glues of slugs

Abstract: SUMMARY The terrestrial slug Arion subfuscus secretes a glue that is a dilute gel with remarkable adhesive and cohesive strength. The function of this glue depends on metals, raising the possibility that metal-catalyzed oxidation plays a role. The extent and time course of protein oxidation was measured by immunoblotting to detect the resulting carbonyl groups. Several proteins, particularly one with a relative molecular mass (Mr) of 165×103, were heavily oxidized. Of the proteins known to disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 30 publications
2
37
1
1
Order By: Relevance
“…Asmp-165 co-elutes more strongly with the carbohydrates, possibly indicating a closer interaction. This is not consistent with previous work that found that asmp-165 was heavily oxidized and appeared to associate with the other high molecular weight proteins in the glue (Bradshaw et al, 2011), though that study did not distinguish between asmp-165 and asmp-220. Further work will be needed to clarify the exact connections between polymers in the glue.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Asmp-165 co-elutes more strongly with the carbohydrates, possibly indicating a closer interaction. This is not consistent with previous work that found that asmp-165 was heavily oxidized and appeared to associate with the other high molecular weight proteins in the glue (Bradshaw et al, 2011), though that study did not distinguish between asmp-165 and asmp-220. Further work will be needed to clarify the exact connections between polymers in the glue.…”
Section: Discussioncontrasting
confidence: 99%
“…Second dimension SDS-PAGE showed that the region at the top of the lane contained a mixture of all the proteins from asmp-40 through to asmp-220, and occasionally some of the proteins identified as asmp-15. Note that proteins are identified as asmp (A. subfuscus mucus protein) followed by the relative molecular mass ×10 −3 (Bradshaw et al, 2011). On a 5% native gel, these proteins ran together with less mobility than a ferritin standard (450 kDa) when they were even able to enter the gel (Fig.…”
Section: Testing For the Presence Of Protein And Carbohydrate Networkmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein oxidation by redox active metals like iron and copper is another way that metals can contribute to a glue (Bradshaw et al, 2011). The oxidation of the rare amino acid 3,4-dihydroxyphenylalanine (dopa), has been studied in depth as a crosslinking step in various biomaterials (Sagert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This typically creates carbonyl groups, which would react readily with the primary amines of other lysine side-chains to form a Schiff base, specifically an imine bond (Tanzer, 1973). Bradshaw et al (Bradshaw et al, 2011) provide evidence that such bonds are present in A. subfuscus glue.…”
Section: Introductionmentioning
confidence: 99%